The effect of shot peening on fatigue and fretting-fatigue of aluminium alloys - Fair, G.H. (1988)
Plain-fatigue and fretting-fatigue tests have been carried out on the two peak-aged, high-strength aluminium alloys, 7010 and 8090, in the unpeened and shot peened conditions.